Host microenvironment in breast cancer development: Extracellular matrix–stromal cell contribution to neoplastic phenotype of epithelial cells in the breast - Shekhar, Malathy PV (BioMed Central, 2003)
Epithelial–mesenchymal interactions play an important role both in normal mammary gland development and during neoplastic transformation. Perturbations in the production, deposition and degradation of the extracellular matrix occurring during neoplastic transformation and progression have been implicated to arise from alterations in the stromal response. These changes in the stroma exhibit a dominant regulatory role, via microenvironmental epigenetic effectors, to contribute to the development of the tumorigenic epithelial phenotype. The role of stromally derived microenvironmental epigenetic effectors in modulating epithelial growth, hormonal response, morphogenesis and epithelial plasticity is discussed.